RE-ACTUALIZATION OF THE COLLECTIVE MEMORY IN THE MODERN UKRAINIAN LITERATURE - Puchońska, Oksana (Porównania, 2014)
The article is dedicated to the peculiarities of the modern Ukrainian culture and literature in the process of post-totalitarian and post-colonialistic studies. The author points to the differences in the concepts of antitotalitarianism and post-totalitarianism, de-colonialism and post-colonialism. She tries to research the representation of the concept of war in the modern Ukrainian literature. Much attention is paid to traumatic memory in the context of Memory Studies. The analysis is carried out on the basis of the following novels: Inge by Sergiy German, Solo for Salomea by Volodymyr Lys and Tango of death by Yuriy Vynnyčuk.